Coleen Nolan's Beauty Secrets : The Real Woman's Guide to Looking Gorgeous, Whatever Your Age, Shape or Size - Nolan, Coleen (London Sidgwick & Jackson, 2010)
Beauty secrets to help you always look and feel fantastic, from Britain's favourite glamorous mum. As a busy working mum, Coleen knows how hard it can be to look good. But she is also lucky enough to have learned many insider tips from years of having worked with some of the country's top stylists and make-up artists. Now she shares her secrets to reveal how any of us can transform ourselves in just minutes from a tired mum in tracksuit bottoms to a glamorous woman ready for a party or a night on the town.
Include Color Illustrations.
The Real Woman's Guide to Looking Gorgeous, Whatever Your Age, Shape or Size.
Keywords: Beauty, Personal